Morphological description of a new species of Capnia (Plecoptera: Capniidae) with DNA barcoding of genus members from the Russian Far East - Teslenko, Valentina A.; Semenchenko, Alexander A. (Zootaxa, 2022)
Capnia yavorskayae, a new species of the stonefly family Capniidae, is described from the Low Amur River Basin, Khabarovskiy Kray of the Russian Far East, on the basis of female morphological features. Confirmation of the uniqueness of the new species was also molecularly compared to other Capnia, including a few Far Eastern species, C. aligera Zapekina-Dulkeit, C. bargusinica Zapekina-Dulkeit, C. khingana Teslenko, C. kurnakovi Zhiltzova, C. nearctica Banks, C. nigra (Pictet), and C. rara Zapekina-Dulkeit for which DNA barcodes were obtained. We support the distinctiveness of the new species with mitochondrial DNA sequences, comparing it to Capnia from the eastern Palaearctic and Nearctic realms and one Zwicknia species. The new species forms a common clade with C. khingana, C. kurnakovi from the Russian Far East, and an undetermined Capnia species from Honshu, Japan. Each species from the Russian Far East has high interspecific distances from other Capnia species except C. nearctica which was close to C. atra Morton.